Subchronic cyanuric acid treatment impairs spatial flexible behavior in female adolescent rats through depressing GluN2B-dependent neuronal and synaptic function - Wei Sun; Haiyang Yu; Xiaoliang Li; Yiwen Wan; Yazi Mei; Yang Yang; Lei An (Ecotoxicology and Environmental Safety)
Subchronic exposure to cyanuric acid (CA) and its structural analogue melamine induces long-term effects on brain and behavior in male rodents. To examine if this exposure induced negative effects on cognitive function in females, we examined the behavioral performance and further attempted to investigate synaptic and neuronal function. CA was intraperitoneal treated with 20 or 40 mg/kg/day to adolescent female rats for 4 consecutive weeks. Multiple behavioral tests were employed to assess spatial cognition, learning strategy, locomotion and motivation. Hippocampal synaptic function at Schaffer collaterals-CA1 synapses and excitatory postsynaptic currents (EPSCs) in CA1 pyramidal neurons was evaluated. Meanwhile, the glutamate transport inhibitor DL-threo-β-benzyloxyaspartate (DL-TBOA) was infused into hippocampal CA1 region to certify the underlying mechanism. We found that subchronic CA exposure impairs reversal learning ability with dose-dependent effects but did not affect spatial learning and memory, or learning strategy. The expression and phosphorylation of N-methyl-D-aspartate receptor (NMDAR) GluN2B subunits were simultaneously reduced in the hippocampus and the GluN2B-mediated synaptic function, including long-term depression (LTD) and paired-pulse facilitation (PPF), was suppressed. CA could also diminish postsynaptic density protein-95 (PSD-95) expression but did change the levels of α-Amino-3-hydroxy-5-methyl-4-isoxazolepropionate receptor (AMPAR) GluA1 or NMDAR GluN2A subunit, or hippocampal spine density. Meanwhile, CA depressed frequency and amplitude of GluN2B-mediated EPSCs, indicating the presynaptic and postsynaptic actions of CA on neuronal activity. Furthermore, the DL-TBOA infusions could effectively mitigate the diminished GluN2B-LTD and GluN2B-EPSCs and the impairments in behavioral flexibility. Our findings provide the first evidence that CA can exert neurotoxic effects on females and certify that one of the potential mechanisms for neuronal and synaptic dysfunction is the GluN2B-mediated signaling pathway.